Diffusion-weighted imaging in gynaecological malignancy. Issue 11 (November 2017) - Addley, H.; Moyle, P.; Freeman, S.
Abstract : Diffusion weighted imaging (DWI) has become an essential part of the gynaecological magnetic resonance imaging (MRI) protocol. DWI is used as an adjunct to conventional MRI sequences and has been shown to improve reporting accuracy in the imaging of gynaecological malignancy. In this review, we discuss the role of DWI in the diagnosis, staging, and assessment of treatment response of endometrial, cervical, and ovarian cancer. We also review the role of DWI in the assessment of the sonographically indeterminate ovarian lesion. Further, we highlight potential pitfalls that can beset the accurate interpretation of DWI in patients with gynaecological malignancy.